(untitled) (Revista Contexto & Saúde, 2025)
Objective: To assess the effectiveness of mechanical ventilation training based on programmed instruction for nurses at a Regional University Hospital in northwest Paraná. Method: A quasi-experimental, before-and-after study, with pre- and post-intervention assessment of a single group, carried out between June and September 2022. Data was collected at three phases: pre-test, immediate post-test, and delayed post-test, the last of which took place three months after the training. The SPSS software was used for analysis, with the Friedman and Durbin-Conover Post-hoc tests. Cronbach’s alpha coefficient was used to analyze the instrument. Results: In the pre-test, 51 nurses participated; in the immediate post-test, participation decreased to 45 nurses, and in the delayed post-test, 30 nurses remained involved in the study. The mean age was 42+7.56 years, 45% of the participants had double jobs, and 64% had never received training on mechanical ventilation. The pre-test had an average score of 8.73+2.21; the immediate post-test had an average score of 12.4+1.87, and the delayed post-test had an average score of 10.7+2.21. Friedman’s test resulted in a p-value <0.01, and Cronbach’s alpha showed that in the delayed post-test, there was better reliability of the questionnaire (value of 0.88). Conclusion: It can be concluded that the training was effective, but three months after it took place, there were still errors that theoretically shouldn’t have been present, highlighting the need for the training to become periodic.